Focus on Opportunities or Limitations? Their Effects on Older Workers’ Conflict Management - Dannii Y. Yeung; Alvin K.-K. Ho (Frontiers in Psychology, 2020)
Socioemotional selectivity theory (SST) stresses that future time perspective (FTP) affects one’s goals and behaviors. In the work context, older workers’ occupational future time perspective (OFTP) also impacts their work-related behaviors. Two studies investigate whether the two components of OFTP, namely, focus on opportunities and on limitations, could account for the age differences in the use of conflict strategies at work. Study 1 comprises 416 Hong Kong Chinese workers aged between 20 and 68 years who completed an online questionnaire measuring their OFTP and habitual use of five conflict management strategies (integrating, compromising, obliging, avoiding, and dominating). In Study 2, 268 managerial employees and professionals were asked to recall a real-life workplace conflict that happened in the past six months and their use of the five conflict strategies in this incident. The results of Study 1 showed a negative indirect effect of age on all five conflict strategies through focus on opportunities, whereas a positive indirect effect of age was observed on obliging, avoiding and dominating strategies through focus on limitations. These age-related patterns are largely replicated in Study 2. These findings suggest that aging workers’ increased perception of limitations make them utilize less constructive strategies when facing conflict at work.